HUBUNGAN PERHATIAN DARI ORANG TUA TERHADAP HASIL BELAJAR SISWA SD KOTA LUBUKLINGGAU - Pristiana Irza (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of carrying out this research is to determine the relationship between parental attention to the learning outcomes of class II SDN 60 Kota Bengkulu Lubuklinggau. Using quantitative correlation. Using a sample of 55 students. Techniques in collecting data using questionnaires and documentation techniques. Techniques in data analysis by applying the formula